Apriori Algorithm Use For A Consumer Behavior In The Purchase Of Goods - Anas, Azwar (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2015)
Data owned by an institution is one of the assets of the institution. Their daily trade transactions will further multiply the number of transaction data. The amount of transaction data so large it could be a problem if traders cannot use it wisely. In this study, researchers will utilize a priori algorithm to group data based on the purchase of goods tendency to appear together in a purchase of goods. The method I use in this case is a priori algorithm. Meanwhile, to conduct tests on the a priori algorithm analysis, the authors use data mining software Orange. The end result of this research is the description of consumer behavior towards the purchase of goods, so that could be a reference to the placement of goods in accordance with their preferences purchased by consumers. In this study the authors simply using a priori algorithm, the authors further expected to be able to combine a couple of similar algorithms, in order to produce more accurate information.